2012
DOI: 10.1103/physrevb.85.195139
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of three-dimensional electrons and transition to two-dimensional transport in the three-dimensional topological insulator Bi2Se3under high pressure

Abstract: American Physical SocietySegura, A.; Panchal, V.; Sánchez-Royo, JF.; Marín-Borrás, V.; Muñoz-Sanjosé, V.; Rodríguez-Hernández, P.; Muñoz, A.... (2012). Trapping of three-dimensional electrons and transition to two-dimensional transport in the three-dimensional topological insulator Bi2Se3 under high pressure. Physical Review B. 85:195139-1-195139-9. doi:10.1103/PhysRevB.85.195139. Abstract. This paper reports an experimental and theoretical investigation on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…(c) After ETT, the CBM and VBM of bulk states are both located at Γ point, which is same as that of surface states, causing a reduction in the separation between surface states and bulk states in the momentum space. However, on the contrary, after ETT, the separation is further enhanced for Bi 2 Te 3 , Bi 2 Se 3 and Sb 2 Te 3 202126.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…(c) After ETT, the CBM and VBM of bulk states are both located at Γ point, which is same as that of surface states, causing a reduction in the separation between surface states and bulk states in the momentum space. However, on the contrary, after ETT, the separation is further enhanced for Bi 2 Te 3 , Bi 2 Se 3 and Sb 2 Te 3 202126.…”
Section: Discussionmentioning
confidence: 90%
“…The orbital composition is almost invariant under selective pressures. This indicates that the TI character should be stable under pressure26. On the other hand, it is found that the increasing interlayer spin-orbit coupling and the fluctuation of LEP activity35 under pressure caused a positive pressure coefficient of indirect band-gap and a reduction in the direct band-gap at Γ point, which result in an indirect-to-direct transition36.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermopower was determined simultaneously using a dc method, where the sample was fixed to a ceramic surface with a small heater attached next to it, and the thermal gradient was determined using a chromel-constantan differential thermocouple. The bulk band gap was determined through transmission and reflection measurements on cleaved thin 57008-p1 flakes, using a Bruker Hyperion microscope, by following the energy of the onset of the Fabry-Perot interferences, similar to the previous high-pressure studies of bismuth chalcogenides [7,10,11]. The behavior of the resistivity throughout the series is shown in fig.…”
mentioning
confidence: 99%